Early Visual Processing and Perception Processes in Object Discrimination Learning - Quiñones, Matías; Gómez, David; Montefusco-Siegmund, Rodrigo; Aylwin, María de la Luz (Frontiers in Neuroscience, 2021)
A brief image presentation is sufficient to discriminate and individuate objects of expertise. Although perceptual expertise is acquired through extensive practice that increases the resolution of representations and reduces the latency of image decoding and coarse and fine information extraction, it is not known how the stages of visual processing impact object discrimination learning. Here we compared object discrimination performance with brief (100 ms) and long (1000 ms) perceptual encoding times to test if the early and late visual processes are required for object discrimination learning. Moreover, we evaluated whether encoding time and discrimination practice shape perception and recognition memory processes during object discrimination learning. During practice of a sequential matching task with initially unfamiliar complex stimuli, we find greater discrimination with greater encoding times regardless of the extent of practice, suggesting that the fine information extraction during late visual processing is necessary for discrimination. Interestingly, the overall discrimination learning was similar for brief and long stimuli, suggesting that early stages of visual processing are sufficient for object discrimination learning. In addition, discrimination practice modulates perceive and know for brief and long stimuli and these processes associate with performance, suggesting that information extraction for brief stimuli is sufficient for modulating the perceptual processes, likely reflecting an increase in the resolution of the representations and an early availability of information. Conversely, practice elicited a moderate increase of familiarity which was not associated with discrimination sensitivity, revealing the acquisition of a general recognition memory. Finally, although the recall is not modulated by practice, it associates with discrimination sensitivity for long encoding times, suggesting the engagement of recognition memory in a practice independent manner. These findings contribute to unveiling the function of early stages of visual processing in object discrimination learning, and provide evidence on the modulation of the perception and recognition memory processes during discrimination practice and its relationship with object discrimination learning and perceptual expertise acquisition.